UPAYA PENINGKATAN KEPERCAYAAN DIRI SISWA SMP 5 MELALUI PROGRAM KAMPUS MENGAJAR 7: INCREASING STUDENTS' CONFIDENCE IN LEARNING MATHEMATICS THROUGH NUMERATION LITERACY CAMPUS TEACHING PROGRAM - Mahendra, Faisal Eka; Hasanudin, Hasanudin; Reawaruw, Marco Filip; Rahmadhani, Nailul Muna; Andini, Rya (Universitas Muhammadiyah Sorong, 2024)
This research aims to increase students' self-confidence in learning mathematics through the